Evidence of major gene(s) affecting milk traits in the Chios sheep breed - Chatziplis, Dimitrios G.; Tzamaloukas, Ouranios; Ligda, Christina; Koumas, Alkis; Mavrogenis, Andreas; Georgoudis, Andreas G.; Miltiadou, Despoina; Papachristoforou, Christakis (My University, 2012)
This study investigates the mode of inheritance and estimates the genetic parameters of milk yield, milk fat content, and litter weight at birth in Chios sheep breed. A complex pedigree and repeated records for milk and fat content as well as litter weight from two distinct and unrelated populations, spanning over 20 and 31 years, were used for the detection of a major gene for milk yield in the Chios breed. The data originated from a closed nucleus in Northern Greece (6021 repeated records) and from a closed nucleus in Cyprus (6965 repeated records). The genetic parameters were estimated using both a polygenic model with maximum likelihood methodology and a mixed inheritance model (polygenes + major gene), using Bayesian segregation analysis. Segregation analysis results support the presence of a major gene for milk yield segregating in both populations. The mixed inheritance model for milk yield appears to be the most suitable model. The estimated additive effect of the putative major gene was 11% and 10.5% of the total additive genetic variance in the Cypriot and Greek populations, respectively, while the estimated dominance effect was negative in both populations. Although there are some indications for a major gene affecting fat content in Chios breed, there is no evidence for the presence of a major gene affecting litter weight at birth in either population
Keywords: Major gene; Milk; Fat; Litter weight; Chios; Segregation analysis